Dynamic Development as the Way of Entrepreneurship Efficiency Increase - G. Shumik, Ekaterina; N. Arnaut, Marina; V. Smitskikh, Ksenia (International Journal of Engineering and Technology, 2018)
The social and economic development of any territory (region, area, municipality) is conditioned by the diverse factors of internal and external environment: federal and regional development programs, the living standards of population, budget investments, the degree of health system development, the territorial peculiarities and many others. In its turn, the level of entrepreneurship development plays an important role in the process of social and economic development of the territory as one of the activities of a person or a circle of people, within which new jobs are created, tax revenues are increased, the spheres of the territory influence and its interaction with various partners are expanded, including foreign ones, the level of innovative developments is growing, etc. At that, within the framework of the present article, the authors will prove that the process of entrepreneurship development occurring within a particular territory must have a dynamic nature that defines it as the trajectory of entrepreneurial activity long-term growth, accompanied by its significant quantitative changes and mutually conditioned qualitative transformations aimed at population life quality improvement. Also, the authors of the article note that the existing mechanisms and approaches to the development, implementation and evaluation of entrepreneurship dynamic development model do not allow to include all stakeholders in this process effectively. Moreover, many authors do not consider this process at all or consider it from the viewpoint of the cyclical nature concerning the emergence of entrepreneurial activity individual subjects, rather than from the standpoint of entrepreneurship process as a whole. The authors made an attempt to determine the factors that influence the process of entrepreneurship dynamic development: economic and subeconomic (personal qualities of an entrepreneur, etc.); to describe the principles that ensure the dynamic development of entrepreneurship: the transition from the management of entrepreneurship development "from above" to the management "from below", the collective responsibility of all stakeholders, the parity of the relations between the business community and the authorities regulating entrepreneurial activity, ensuring the continuity of generations for the development of long-term entrepreneurial activity, the focus on the scope of business expansion; to describe the model ensuring the dynamic development of entrepreneurship and provide the algorithm for its effectiveness evaluation; to identify stakeholders that directly affect the dynamic development of entrepreneurship and include foreign partners in their composition as the prerequisite ensuring the qualitative functioning of the designated process model and its effectiveness evaluation, taking into account the territorial peculiarities described in the article of the Far Eastern Federal District of Russia (FEFD). Â